Remarks on Receiving the John K. Knutson Distinguished - Viron L. Diefenbach, DDS, MPH (Blackwell Synergy, 2000)
Ahhhhh! There, in the back of the room, is that an image? YES! ... there’s an image and it’s becoming clear ... Yes, now I see a trim, handsome man and he’s smiling! ... He’s standing, tan with dark hair, and good looking with a devilish grin. It’s John Knutson! And he’s looking at me just as he did in Washington, DC, 45 years ago.